2004
DOI: 10.1002/bip.20086
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the N‐terminal mineral modification domains from the molluscan crystal‐modulating biomineralization proteins, AP7 and AP24

Abstract: The AP7 and AP24 proteins represent a class of mineral-interaction polypeptides that are found in the aragonite-containing nacre layer of mollusk shell (H. rufescens). These proteins have been shown to preferentially interfere with calcium carbonate mineral growth in vitro. It is believed that both proteins play an important role in aragonite polymorph selection in the mollusk shell. Previously, we demonstrated the 1-30 amino acid (AA) N-terminal sequences of AP7 and AP24 represent mineral interaction/modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
125
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(141 citation statements)
references
References 43 publications
16
125
0
Order By: Relevance
“…Mammals DMP1 4.0 CD, DLS, FTIR, SAXS (Gericke et al, 2010;He et al, 2003aHe et al, , 2003b DPP 2.8 CD, NMR, SAXS (Cross et al, 2005;Evans et al, 1994;Fujisawa & Kuboki, 1998;George & Hao, 2005;He et al, 2005b;Lee et al, 1977) BSP 4.1 CD, NMR, SAXS (Fisher et al, 2001;Tye et al, 2003Tye et al, , 2005Wuttke et al, 2001) OPN 4.4 CD, NMR, FTIR (Fisher et al, 2001;Gorski et al, 1995) amelogenin 6.6 CD, NMR (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011;Shaw et al, 2008) statherin 8.0 CD, NMR (Long et al, 2001;Naganagowda et al, 1998;Raj et al, 1992) lithostathine 5.7 CD (Gerbaud et al, 2000) Haliotis rufescens AP7 5.2 CD, NMR (Kim et al, 2004(Kim et al, , 2006aMichenfelder et al, 2003;Wustman et al, 2004) Atrina rigita Asprich 2.7-3.5 CD, NMR (Collino et al, 2006;Delak et al, 2009aDelak et al, , 2008Kim et al, 2008;Ndao et al, 2010) Procambrus clarkii CAP-1 3.9 CD (Inoue et al, 2007) Strongylocentrotus purpuratus SM50 10.8 CD, NMR (Xu & Evans, 1999;Zhang et al, 2000) PM27 8.1 CD, NMR Danio rerio Stm 4.1 CD, gel filtration (Kaplon et al, 2008(Kaplon et al, , 2009 Table 1. IDPs involved in biomineralization of calcium carbonate and phosphate for which a disordered structure has been confirmed...…”
Section: Protein Pi Methods Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Mammals DMP1 4.0 CD, DLS, FTIR, SAXS (Gericke et al, 2010;He et al, 2003aHe et al, , 2003b DPP 2.8 CD, NMR, SAXS (Cross et al, 2005;Evans et al, 1994;Fujisawa & Kuboki, 1998;George & Hao, 2005;He et al, 2005b;Lee et al, 1977) BSP 4.1 CD, NMR, SAXS (Fisher et al, 2001;Tye et al, 2003Tye et al, , 2005Wuttke et al, 2001) OPN 4.4 CD, NMR, FTIR (Fisher et al, 2001;Gorski et al, 1995) amelogenin 6.6 CD, NMR (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011;Shaw et al, 2008) statherin 8.0 CD, NMR (Long et al, 2001;Naganagowda et al, 1998;Raj et al, 1992) lithostathine 5.7 CD (Gerbaud et al, 2000) Haliotis rufescens AP7 5.2 CD, NMR (Kim et al, 2004(Kim et al, , 2006aMichenfelder et al, 2003;Wustman et al, 2004) Atrina rigita Asprich 2.7-3.5 CD, NMR (Collino et al, 2006;Delak et al, 2009aDelak et al, , 2008Kim et al, 2008;Ndao et al, 2010) Procambrus clarkii CAP-1 3.9 CD (Inoue et al, 2007) Strongylocentrotus purpuratus SM50 10.8 CD, NMR (Xu & Evans, 1999;Zhang et al, 2000) PM27 8.1 CD, NMR Danio rerio Stm 4.1 CD, gel filtration (Kaplon et al, 2008(Kaplon et al, , 2009 Table 1. IDPs involved in biomineralization of calcium carbonate and phosphate for which a disordered structure has been confirmed...…”
Section: Protein Pi Methods Referencementioning
confidence: 99%
“…Far-UV CD studies of AP7 showed that the N-terminus of AP7 adopts a random-coil or extended conformation in solution (Tab 1.) (Michenfelder et al, 2003;Wustman et al, 2004), while the C-terminus is -helical (Kim et al, 2006a). Interestingly, AP7's C-terminus end did not influence crystal growth (Kim et al, 2006a), while AP7's N-terminus was responsible for interactions with calcium ions and led to an inhibition of calcite growth in vitro (Kim et al, 2004;Michenfelder et al, 2003).…”
Section: Mollusk Shell Proteinsmentioning
confidence: 99%
“…There are no consistent compositions or structural homologs found amongst these organic fractions, except that they do have regions which are highly repetitive and have characteristics of "intrinsically disordered protein" (IDP) domains, domains implicated in either mineral binding or the assembly process [23][24][25]. Many have associated these IDPs to being active participants in various biological processes like biomineralization [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used to examine the participation of a number of polypeptides within biomineral nucleation and crystal growth assay systems. [9][10][11][12][13][14][15][16][17] Although limited in their scope, such in vitro systems provide much needed information on the role of proteins within mineralizing systems, and can serve as a stepping stone towards more complex model systems that possess larger numbers of molecular participants.…”
mentioning
confidence: 99%
“…9,11,[13][14][15][16][17] To examine the molecular features present at the OMI in the organic-mineral systems, we used x-ray absorption near-edge structure (XANES) spectroscopy, a tool sensitive to the electronic and molecular structure. Although XANES cannot provide the complete molecular or mineral three-dimensional structure that diffraction yields, it is exquisitely sensitive to the formation or disruption of chemical bonds, does not require the sample to be crystalline, and can analyze both sides of the OMI in these model systems.…”
mentioning
confidence: 99%